Vontade de verdade e as “metamorfoses do Niilismo”, em Nietzsche - Moraes, João Miguel de (2017)
Nietzsche's thinking strives to denounce that on the basis of truth there is no metaphysical foundation that will support it and ensure its validity, but a "will" to make fixed, consistent, eternal and unchanging what is in permanent change. By problematizing this will, Nietzsche asserts that "nothing is more dangerous than a desire that contradicts the essence of life," for it was precisely from the metaphysical fabulations of this will that the great problem of the West unfolded: "nihilism." Since nihilism is what constitutes the "logic" of the historical process, we will seek to understand how its formation took place, as well as the paths taken by the philosopher for a possible overcoming of that prevailing "no" to life. From the perspective that nihilism is not a uniform but complex and dynamic phenomenon, because it undergoes various "metamorphoses" throughout its historical development, we will seek to understand and explain how each of its forms and possible relations and tensions are constituted between them and the will of truth. We understand that although such tensions and relations are not systematically presented in their works, it would be possible to combine the notes and reflections developed in their writings to support our interpretation that the historical origin, development and "consummation" of nihilism in modernity, as well as their possible overcoming, are directly related to the "will to truth". Finally, we will try to understand how the philosopher, in problematizing the will of truth and nihilism from the concept of "will to power", seeks to transfigure the "no" that marked the trajectory of the West in a great "yes" to life .